2006
DOI: 10.1103/physrevb.73.125402
|View full text |Cite
|
Sign up to set email alerts
|

All-electron first-principles investigations of the energetics of vicinal Cu surfaces

Abstract: Using first-principles calculations we studied the energetics ͑surface energy, step energy, stability with respect to faceting͒ of the low-and high-Miller-index ͑vicinal͒ Cu surfaces, namely, the ͑111͒, ͑100͒, ͑110͒, ͑311͒, ͑331͒, ͑210͒, ͑211͒, ͑511͒, ͑221͒, ͑711͒, ͑320͒, ͑553͒, ͑410͒, ͑911͒, and ͑332͒ surfaces. Our calculations are based on density-functional theory employing the all-electron full-potential linearized augmented planewave ͑FLAPW͒ method. We found that the unrelaxed vicinal Cu surfaces between … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
46
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 56 publications
(55 citation statements)
references
References 42 publications
(64 reference statements)
9
46
0
Order By: Relevance
“…6,7,30) Recent ab initio calculations also indicate that the surface energy of Cu (110) is 0.901 eV per surface atom in contrast to 0.708 eV (78%) for Al(110). 31,32) Thus the present results of the smaller boundary energies for Al than for Cu are consistent with other types of defect energies.…”
Section: Comparison Between Al and Cusupporting
confidence: 89%
“…6,7,30) Recent ab initio calculations also indicate that the surface energy of Cu (110) is 0.901 eV per surface atom in contrast to 0.708 eV (78%) for Al(110). 31,32) Thus the present results of the smaller boundary energies for Al than for Cu are consistent with other types of defect energies.…”
Section: Comparison Between Al and Cusupporting
confidence: 89%
“…An analogous situation exists for step energies of vicinal Cu(111) surfaces [17]. We evaluated the Cu first principles surface energies in the 110 zone according to (1) and obtained excellent straight lines whose slopes correspond to the formation energies of A and B steps of Cu(111).…”
Section: Comparison Of Theory and Experimentsmentioning
confidence: 83%
“…In the general context of the broken bond model mentioned above it has been suggested that surface energies of vicinal orientations may not have to be calculated but instead be estimated by assuming a strict linear relationship between values calculated for low-index surfaces and the number of broken bonds for any vicinal surface [17]. However, this degree of simplification is most likely leading to unreliable results when it comes to a description of properties of vicinal surfaces [9,63].…”
Section: Orientation Dependent Surface Energies and Ecs Of Pb By Firsmentioning
confidence: 99%
See 2 more Smart Citations